Pelatihan Kerajinan Tangan Kimekomi sebagai Implementasi Seni dan Budaya Tradisional Jepang bagi Siswa SMKN 9 Padang - Putri, Meira Anggia; Faisal, Dini; Fitriyona, Nessya (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2025)
This community service program was carried out to introduce and train students in kimekomi, a traditional Japanese handicraft, as part of the integration of language, art, and culture in learning Japanese. The activity was conducted at SMKN 9 Padang and involved 27 students. The training employed an educational and creative approach through lectures, discussions, demonstrations, and guided as well as independent practice. Two main aspects were emphasized: (1) students’ knowledge of kimekomi as a traditional Japanese cultural art, and (2) students’ skills in producing kimekomi handicrafts. The results showed a significant improvement in students’ knowledge. The average score increased from 52.3 (pretest) to 87.3 (posttest), with the mode shifting from 50 to 80, and the median rising from 50 to 90. The standard deviation decreased from 21.59 to 9.6, indicating that students’ achievements became more evenly distributed. In terms of skills, all participants successfully completed their kimekomi works according to the given patterns and demonstrated adequate craftsmanship through guided and independent practice. In conclusion, the kimekomi training program proved effective in improving both cognitive and practical aspects of students’ learning. It not only enhanced their understanding of Japanese cultural heritage but also fostered creativity and productivity through hands-on artistic activities.